Cultivating Morals Students through Character Education: A Case Study - Anzar Abdullah (Intelektual Pustaka Media Utama, 2018)
This research aims to describe: First, the application of character education in SMP Negeri 16 Makassar. Second, the impact of the application of character education the school in SMP Negeri 16 Makassar. This was a qualitative research employing the naturalistic approach, carried out in SMP Negeri 16 Makassar. The data were collected through observations in debt interview, and document. The research finding, the following conclusions are drawn: (1). The development of school culture to build character in SMP Negeri 16 Makassar, consisting of planning, application, supervision, and evaluation, runs well. The application of character education in SMP Negeri 16 Makassar runs well, supported by the school personal and school committee. (2). The impacts of character, among others, manifested in: caring cleanliness; religious service obedience; conformity to the rules; mutual respect politeness, and family like relationship; honesty and responsibility; togetherness; and all personal school, including teacher and staff participation.